Methodological Problems in Accounting and Bookkeeping of Environmental Costs - Yonkova, Boichinka (Research Papers, 2007)
This study aims at analyzing and discussing some basic methodological issues, concerning the accounting treatment and reporting of costs of environment protection, organizational change and its management. At this stage of social development, the issues of environment protection both on EU and national level are becoming ever more significant. The problems of environment protection, and mainly the financing of the measures for the conduct of the environmental policies, their reporting and control, determine the topicality of the issue discussed in this study.The increasing productions costs of environment protection at the end of last century and the growing innovative pressure on a global scale, the reporting and analysis of ecological issues have acquired higher importance. The attention toward this topic has increased as a result of the successful examples of the production practice, which show that due to the protection of the environment, the overall costs of enterprises have generally declined. Some major categories, concepts and methods of reporting environment protection costs have been considered.